(untitled) (Journal of the Bangladesh Agricultural University, 2012)
We assessed the prevalence and seasonal variations of intestinal schistosomiasis in association with age, sex, breed and rearing system of cattle and goats in different districts of Bangladesh. Fecal samples from 240 cattle and 146 goats were examined. Schistosoma eggs were found in 47.5% cattle and 43.84% goats. Two species of schistosomes were identified. No mixed infection was recorded. Prevalence of Schistosoma indicum was higher in cattle (42.5%) than in goats (34.25%) whereas goats (9.59%) were more susceptible to Schistosoma spindale infection than cattle (5.0%). Age, sex, breed, rearing system and topography of the country had significant (P<0.01, P<0.05) effect on the prevalence of schistosomiasis among cattle, whether only seasons of the year had significant (P<0.01) effect on schistosome prevalence among goats of Bangladesh. Higher infection rate was found in rainy season, in older age group, in males, in local breeds (cattle) and animals reared under semi intensive system. Prevalence was highest in the Rangpur district and lowest in the Dhaka district. The prevalence of intestinal schistosomiasis was very high among cattle and goats in the study area irrespective of age, sex, breed, seasons and rearing system of cattle and goats. DOI: http://dx.doi.org/10.3329/jbau.v9i2.10990 J. Bangladesh Agril. Univ. 9(2): 221228, 2011